Death in Henry James - Cutting, A. author. aut Link
IX, 198 p.
Keywords: Moving beyond established ideas of haunted Henry James, this book argues that death is as important a concept for understanding James's fiction as gender, sexuality and modernity, which have come to dominate James studies. Combining formal analysis and close reading with theoretical and historical approaches and focusing on key novels and tales from across James's career, Andrew Cutting explores five instances of Jamesian death: sacrifice, the corpse, morbidity, afterlife and demography. This is the first full-length study of this subject.